Práticas de análise estrutural no Membro Assistência - Formação Irati, em Saltinho-SP: estudos de campo e aplicação de tomografia elétrica - Lacerda, Katarine Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Studies focused on structural geology developed in the rocks of the Irati Formation allowed the identification of large fault systems related to the accumulation of hydrocarbons. The area of interest is inserted in the stratigraphic-structural context of the Paraná Basin, associated with the Tietê Lineament (NW-SE) and the Serrote structure, located SE of the High Structural of Jibóia. In this work, the Cava Monte Olimpo of Mineradora Amaral Machado in Saltinho - SP was selected for the identification of fault systems of regional amplitude. In the study area, there is intercalation of shales with high levels of organic matter and centimeter layers of limestone from the Irati Formation, and covering these rocky packages, there are claystones and siltstones from the Corumbataí Formation. The region is conditioned by large normal-type fault systems. At the macroscopic level, these faults are oriented according to the preferred NW-SE direction, present dips of 60° to NE and SW and have associated tailings of 10 to 3 meters. At the mesoscopic level, there is a system of faults with centimeter tailings, extensional joints and fractures, carbonate breccias, and cavities filled with hydrocarbons. The work evolves from bibliographic geological-structural data, structural data collected in the field, and geophysical data collected from the electrical tomography method. The results generated from the electrical imaging allowed the identification of the main structures in the NW-SE direction, as observed in the field activities, mainly the synthetic faults along all the sections, where it was possible to observe the large diving tailings of the plane of faults, delimit the contact between the lithologies and recognize little fractured and altered portions of the rock mass. The integration of the data collected at the Monte Olimpo mine front with the electrical tomography data allowed the association of these main structures with NW-SE orientation, with the Tietê Lineament and the Serrote structure (High Structural of Jibóia). And this structure identified in the Irati Formation presents faults favorable to the percolation of fluids and portions of the bedding that limit its permeability, behaving as conduits or barriers for the migration of hydrocarbons.

Os estudos com foco em geologia estrutural desenvolvidos nas rochas da Formação Irati permitiram a identificação de grandes sistemas de falhas relacionados à acumulação de hidrocarbonetos. A área de interesse é inserida no contexto estratigráfico-estrutural da Bacia do Paraná, associada ao Lineamento Tietê (NW-SE) e a estrutura do Serrote, localizado a SE do Alto Estrutural de Jibóia. Nesse trabalho foi selecionado a Cava Monte Olimpo da Mineradora Amaral Machado em Saltinho – SP, para a identificação de sistemas de falhas de amplitude regional. Na área de estudo ocorre a intercalação de folhelhos com altos teores de matéria orgânica e camadas centimétricas de calcários da Formação Irati, e recobrindo estes pacotes rochosos, há os argilitos e siltitos da Formação Corumbataí. A região é condicionada por grandes sistemas de falhas do tipo normal. Em nível macroscópico essas falhas são orientadas segundo a direção preferencial NW-SE, apresentam mergulhos de 60° para NE e SW e possuem rejeitos associados de 10 a 3 metros. Em nível mesoscópico ocorre sistema de falhas com rejeitos centimétricos, juntas e fraturas extensionais, brechas carbonáticas e cavidades preenchidos por hidrocarbonetos. O trabalho evolui a partir de dados geológicosestruturais bibliográficos, dados estruturais coletados em campo e dados geofísicos levantados a partir do método da tomografia elétrica. Os resultados gerados a partir do imageamento elétrico permitiram a identificação das estruturas principais de direção NW-SE, conforme observadas nas atividades de campo, principalmente as falhas sintéticas ao longo de todas as seções, onde foi possível observar os grandes rejeitos de mergulho do plano de falhas, delimitar o contato entre as litologias e reconhecer porções pouco fraturadas e alteradas do maciço rochoso. A integração dos dados coletados na frente de lavra Monte Olimpo com os dados de tomografia elétrica permitiu associar essas estruturas principais de orientação NWSE, com o Lineamento Tietê e a estrutura de Serrote (Alto Estrutural de Jibóia). E essa estrutura identificada na Formação Irati apresenta falhas favoráveis à percolação de fluidos e porções do acamamento que limitam a sua permeabilidade, comportando-se como condutos ou barreiras para a migração dos hidrocarbonetos.
Structural analysis practices in the Assistance Member - Irati Formation, in Saltinho-SP: field studies and application of electrical tomography
Keywords: Structural analysis; Electrical tomography; Irati Formation; Análise estrutural; Tomografia elétrica; Formação Irati